Left Main Compression by a Giant Aneurysm of the Left Sinus of Valsalva: An Extremely Rare Reason for Myocardial Infarction and Cardiogenic Shock - Bruno L. R. Faillace; Micheli Z. Galon; Marcos Danillo P. Oliveira; Guy F. A. Prado; Adriano A. M. Truffa; Expedito E. Ribeiro; Pedro A. Lemos (Case Reports in Cardiology)
Aneurysms of the sinus of Valsalva are very rare and mostly located in the right coronary sinus. They might course with dyspnea, fatigue, and acute coronary syndromes. We present herein an extremely rare case report of a 61-year-old woman diagnosed with external left main coronary compression by a giant aneurysm of the left sinus of Valsalva, which was successfully managed with percutaneous coronary intervention.